2014
DOI: 10.3389/fmars.2014.00062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ocean acidification and warming on the Mediterranean mussel (Mytilus galloprovincialis)

Abstract: In order to assess the effects of ocean acidification and warming on the Mediterranean mussel (Mytilus galloprovincialis), specimens were reared in aquarium tanks and exposed to elevated conditions of temperature (+3 • C) and acidity (−0.3 pH units) for a period of 10 months. The whole system comprised a factorial experimental design with 4 treatments (3 aquaria per treatment): control, lowered pH, elevated temperature, and lowered pH/elevated temperature. Mortality was estimated on a weekly basis and every 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 49 publications
(46 reference statements)
5
63
1
Order By: Relevance
“…This supports the observations by that both fluids are characterized by a similar carbonate system, also recently described in M. galloprovincialis (Gazeau et al, 2014). Therefore, only haemolymph data are discussed here.…”
Section: Thermal Limits Under Normocapniasupporting
confidence: 91%
“…This supports the observations by that both fluids are characterized by a similar carbonate system, also recently described in M. galloprovincialis (Gazeau et al, 2014). Therefore, only haemolymph data are discussed here.…”
Section: Thermal Limits Under Normocapniasupporting
confidence: 91%
“…Previous experiments that focused on the effect of ocean acidification on bivalve calcification assumed that NH 4 + excretion is negligible (Gazeau et al 2007, Mingliang et al 2011, Waldbusser et al 2011. Recently, however, Gazeau et al (2014) reported NH 4 + excretion rates being responsible for 60% (on average) of ΔA T in the Mediterranean mussel Mytilus galloprovincialis kept in the laboratory for ~1 yr. This contribution is much higher than that reported in the present study, suggesting that correction of ΔA T could vary significantly depending on the physiological state of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…It is nondestructive and offers the possibility of studying the same organism and following its calcification over time (e.g. Martin & Gattuso 2009, Bramanti et al 2013, Gazeau et al 2014). Another option is to estimate the linear extension (growth) of an organism, assuming the density of its calcifying structures is known.…”
Section: Introductionmentioning
confidence: 99%
“…Seawater warming may ameliorate the negative impact of seawater acidification on corals (Kleypas and Yates, 2009;McNeil et al, 2004). Whether the combination of seawater acidification and elevated temperature affects shell growth, metabolic rate and periostracum production in the Mediterranean mussel, Mytilus galloprovincialis, is unclear (Gazeau et al, 2014). These results suggest that there are complex responses within different calcifiers to the combined climate stressors.…”
Section: Introductionmentioning
confidence: 98%